Intercultural communication competence and job burnout in MNC employees: the mediation role of job stress - Xie, Xiaoxia; Tu, Yulu; Huang, Chienchung (Frontiers in Psychology, 2024)
This study examined the relationship between intercultural communication competence (ICC) and job burnout, as well as the mediating effects of job stress using data collected from employees (n=1,064) from a Chinese multinational cooperation in Brunei. Through regression analysis and mediation effect tests, we found that ICC was negatively associated with job burnout (β=-0.19, p<0.001) and job stress (β=-0.08, p<0.001). Job stress was positively associated with job burnout (β=0.65, p<0.001). Job stress played a partial mediating effect between ICC and job burnout. The total effect of ICC on job burnout was -0.19, the direct effect was -0.14 and the indirect effect of ICC via job stress was -0.05. The findings call for ICC training for employees in multinational cooperation.